2019
DOI: 10.3390/pharmaceutics11070338
|View full text |Cite
|
Sign up to set email alerts
|

Design of Soft Nanocarriers Combining Hyaluronic Acid with Another Functional Polymer for Cancer Therapy and Other Biomedical Applications

Abstract: The rapid advancement in medicine requires the search for new drugs, but also for new carrier systems for more efficient and targeted delivery of the bioactive molecules. Among the latter, polymeric nanocarriers have an increasingly growing potential for clinical applications due to their unique physical and chemical characteristics. In this regard, nanosystems based on hyaluronic acid (HA), a polysaccharide which is ubiquitous in the body, have attracted particular interest because of the biocompatibility, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 84 publications
(178 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ]. The structure of HA can be modified to produce a variety of derivatives, which not only maintains its stability, but also enhances its bio-compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ]. The structure of HA can be modified to produce a variety of derivatives, which not only maintains its stability, but also enhances its bio-compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nanocarriers have been adopted as a preferred method for drug delivery, as they offer solutions to overcome many problems of the actual therapies. [ 1 ] Many polymeric nanocarrier‐based drugs have been applied in clinical practice and have made significant contributions to the treatment of diseases such as hepatitis, chronic kidney disease, and oncology. [ 2 ] However, the inefficient delivery of polymeric nanocarriers to target pathological tissues limits their widespread application, especially in the field of tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tended to study gene transfection systems that protect DNA from nuclease damages in intra/extracellular environments 12 . Many researchers have addressed polymeric gene nanocarriers (NCs) 13–15 . Cationic polymers such as poly‐L‐lysine (PLL), poly ethyleneimine (PEI), and carbohydrates‐derived polymers such as chitosan, electrostatically interact with negatively charged DNA to form polyplexes with 100–200 nanometre diameters 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Many researchers have addressed polymeric gene nanocarriers (NCs). [13][14][15] Cationic polymers such as poly-L-lysine (PLL), poly ethyleneimine (PEI), and carbohydrates-derived polymers such as chitosan, electrostatically interact with negatively charged DNA to form polyplexes with 100-200 nanometre diameters. [16][17][18] Positively charged PLL con-denses DNA by polyplex formation through the electrostatic interaction between the primary amine of lysine in PLL and the phosphate groups in DNA.…”
Section: Introductionmentioning
confidence: 99%